Sex Recession: Challenges and Threats for the Economy - Lusiana Lusiana; Fauziah Fauziah; Wasti Indah Haryani Daulay (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2023)
The term "sex recession" refers to a decline in the willingness to engage in sexual intercourse and, consequently, a reluctance to marry and have offspring. This phenomenon is prevalent in many developed countries, leading to a notable decrease in birth rates and a slowed regeneration process. The long-term impacts of sex recession extend beyond demographic shifts and pose challenges to economic dynamics. As population declines, there is a gradual reduction in consumer needs, resulting in diminished purchasing power and imbalances in supply and demand. This economic passivity poses a significant threat to future economic sustainability. This study employs a phenomenological approach and conducts a comprehensive literature review to explore the multifaceted implications of the sex recession phenomenon. The findings highlight the potential long-term challenges and threats to economic development, emphasizing the urgency of research in this domain to inform strategic interventions and policy decisions.